2010
DOI: 10.2193/2008-551
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Golden‐Cheeked Warblers on Private Lands in Texas

Abstract: A majority of North American breeding habitat for neotropical migrants exists on private lands, requiring monitoring strategies focused on habitat in these private holdings. We outline study designs and protocols using repeated presence-absence surveys across a gradient of patch sizes to develop a range-wide monitoring program for the endangered golden-cheeked warbler (Dendroica chrysoparia) in Texas, USA. We surveyed 200-400 point-count locations across approximately 30 private properties annually from 2005 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…We also found strong support for our prediction that proportion of forest cover affected density positively, which is consistent with patterns in Golden-cheeked Warbler occurrence (DeBoer and Diamond 2006, Magness et al 2006, Collier et al 2010, as well as with abundance of other migratory passerines nesting in forest (Flather and Sauer 1996, Howell et al 2000, Thompson et al 2012. A positive relationship between density and proportion of forest cover could be a bird's response to increased quantity of suitable habitat (Whitcomb et al 1981, Temple andCary 1988) or to factors that affect habitat quality, such as microhabitat characteristics (Lynch and Whigham 1984), food availability (Blake 1983, Burke andNol 1998), or changes in levels of nest prédation associated with proportion of forest cover , Robinson et al 1995, Tewksbury et al 1998) and its effect on the abundance and activity patterns of nest predators (Donovan et al 1997, Chalfoun et al 2002.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We also found strong support for our prediction that proportion of forest cover affected density positively, which is consistent with patterns in Golden-cheeked Warbler occurrence (DeBoer and Diamond 2006, Magness et al 2006, Collier et al 2010, as well as with abundance of other migratory passerines nesting in forest (Flather and Sauer 1996, Howell et al 2000, Thompson et al 2012. A positive relationship between density and proportion of forest cover could be a bird's response to increased quantity of suitable habitat (Whitcomb et al 1981, Temple andCary 1988) or to factors that affect habitat quality, such as microhabitat characteristics (Lynch and Whigham 1984), food availability (Blake 1983, Burke andNol 1998), or changes in levels of nest prédation associated with proportion of forest cover , Robinson et al 1995, Tewksbury et al 1998) and its effect on the abundance and activity patterns of nest predators (Donovan et al 1997, Chalfoun et al 2002.…”
Section: Discussionsupporting
confidence: 87%
“…Occurrence was positively associated with density of edges at the 100-m scale but negatively associated with it at the larger scales. Collier et al (2010) found that probability of patch occupancy was positively associated with patch size and predicted that all patches >160 ha should be occupied. These models are useful tools that managers can use to determine the spatial distribution of habitat where Golden-cheeked Warblers are likely to occur and hence provide important insight for habitat management and recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Collier et al . ). These models have also been implemented within a hierarchical framework, which allows for the separation of the observation model and the ecological process model while including both sources of uncertainty in estimates of variance pertaining to parameters of interest (Royle & Kéry ; Royle & Dorazio ).…”
Section: Introductionmentioning
confidence: 97%
“…Further, information concerning more recent habitat dynamics across the entire warbler breeding range is lacking. An up-to-date understanding of the dynamics of warbler breeding habitat patch metrics is particularly important since increased forest edge, decreased habitat patch size, and reduced connectivity of habitat patches have been linked to deleterious effects on warbler reproductive success (Peak 2007, Reidy et al 2009, increased genetic differentiation among warbler populations (Lindsay et al 2008), a decline in genetic diversity over time (Athrey et al 2011), and reduced warbler occupancy of habitat patches (Collier et al 2010, Warren et al 2013. Notably, habitat patches with lower occupancy probabilities have been reported to support lower warbler abundances The objective of this study was to model rangewide warbler breeding habitat dynamics from 2000 to 2010 using available GIS data and Landsat imagery.…”
Section: Introductionmentioning
confidence: 99%